Hubungan antara Kesiapan Menghadapi Perubahan, Persepsi Dukungan Organisasi, Psychological Capital dan Stress Kerja ASN di Lingkungan Pemerintah Provinsi Jawa Timur di Kota Surabaya - Puspita, Arum Listya; Suroso, Suroso; Santi, Dyan Evita (Guidena, 2024)
This research aims to determine the relationship between Readiness to Change, Perception of Organizational Support, Psychological Capital, and Job Stress in ASN within the East Java Provincial Government in the City of Surabaya. This research uses quantitative correlational research methods. The population of this research is ASNs who work in East Java Province, where their work area is in the City of Surabaya. A research sample of 238 subjects was obtained from various regional apparatus organizations in East Java Province, with functional and staff positions. The data collection method uses a scale adapted from the work stress scale, readiness to change scale, perception of organizational support scale, and psychological capital scale. This research has tested classical assumptions using normality, linearity, and multicollinearity tests. The data obtained was analyzed using multiple regression analysis. In the variable readiness to face changes to work stress, a t value of -5.629 was received with a significance level of 0.000 (p<0.05); it can be concluded that the variable readiness to face changes is correlated with work stress in a negative direction. In the variable perception of organizational support and work stress, a t value of -2.384 was obtained with a significance level of 0.018 (p<0.05). It can be concluded that the variable perception of organizational support is correlated with work stress in a negative direction. In the psychological capital variable with work stress, a t value of -4.984 was obtained with a significance level of 0.000 (p<0.05), so it can be concluded that psychological capital is correlated with work stress with an antagonistic relationship